2010
DOI: 10.1074/jbc.m109.079525
|View full text |Cite
|
Sign up to set email alerts
|

MiR-148a Attenuates Paclitaxel Resistance of Hormone-refractory, Drug-resistant Prostate Cancer PC3 Cells by Regulating MSK1 Expression

Abstract: MicroRNAs are involved in cancer pathogenesis and act as tumor suppressors or oncogenes. It has been recently reported that miR-148a expression is down-regulated in several types of cancer. The functional roles and target genes of miR-148a in prostate cancer, however, remain unknown. In this report, we showed that miR-148a expression levels were lower in PC3 and DU145 hormone-refractory prostate cancer cells in comparison to PrEC normal human prostate epithelial cells and LNCaP hormone-sensitive prostate cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
135
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(142 citation statements)
references
References 38 publications
(30 reference statements)
6
135
1
Order By: Relevance
“…They play an important role in biological processes23 and are broadly involved in tumour proliferation, invasion, angiogenesis and drug resistance 25, 26, 27. MiRNAs such as miR‐148a,27 miR‐200c,28 miR‐205,28 miR‐2129 and miR‐3430 have been reported to modulate drug resistance of PCa. Recent studies have demonstrated that miR‐145‐5p is down‐regulated in several cancer types, including bladder cancer,31 breast cancer,32 colon cancer 33 and ovarian cancer,34 indicating that it is a tumour‐suppressive miRNA.…”
Section: Introductionmentioning
confidence: 99%
“…They play an important role in biological processes23 and are broadly involved in tumour proliferation, invasion, angiogenesis and drug resistance 25, 26, 27. MiRNAs such as miR‐148a,27 miR‐200c,28 miR‐205,28 miR‐2129 and miR‐3430 have been reported to modulate drug resistance of PCa. Recent studies have demonstrated that miR‐145‐5p is down‐regulated in several cancer types, including bladder cancer,31 breast cancer,32 colon cancer 33 and ovarian cancer,34 indicating that it is a tumour‐suppressive miRNA.…”
Section: Introductionmentioning
confidence: 99%
“…23 It has been recently shown that the overexpression of miR-148a precursor inhibited the growth of androgen-refractory PC3 cells, and even paclitaxel-resistant PC3 cells by repressing an miR-148a target mitogen-and stress-activated protein kinase 1. 24 It is interesting that ectopic miR-148a functions as a tumor suppressor in androgen-refractory PC3 cells, which originally contains a smaller amount of miR-148a than androgen-sensitive LNCaP cells. We consider that miR148a expression would be altered during the progression of cancer stages.…”
Section: Discussionmentioning
confidence: 99%
“…exhibited the regulation pattern of stage-specific increasing expression with a dramatic reduction of expression in lymph node metastasizing prostate carcinoma. We, furthermore, selected miRNAs miR-15a and miR-148a because the functional role of these miRNAs in primary prostate carcinoma cases is currently under discussion (18)(19)(20). The changes in the expression levels of let-7c, miR-15a, miR-20a, miR-143, miR-145, miR-148a, miR-200b, and miR-375 observed by sequencing were analyzed by Northern blot analysis of the pooled RNAs employed in the generation of the cDNA libraries for sequencing as shown in Supplementary Fig.…”
Section: Mirna Profiling Of Normal Prostate Tissues and Prostate Carcmentioning
confidence: 99%
“…2 and 3). miRNAs are short, noncoding RNAs of approximately [19][20][21][22][23][24][25] nucleotides that bind preferentially to specific sequences in the 3 0 -untranslated region (3 0 UTR) of mRNAs, resulting in either translational repression or mRNA degradation. Interaction of the miRNAs with their mRNA target ultimately leads to reduced protein synthesis via association with the Argonaute (Ago-) containing RNAinduced silencing complex (for a review, see ref.…”
Section: Introductionmentioning
confidence: 99%